MISSIONAL-DIACONAL PRACTICES IN JAPAN AND SOUTH AFRICA: - J.S. Van der Watt (Acta Theologica)
This article reflects on missional-diaconal practices in the ecumenical partnership between the Dutch Reformed Church in South Africa and the Reformed Church in Japan. In both – albeit radically different – contexts, the issue of church formation in a secular age is at stake. How can these Reformed faith communities remain relevant in their respective societies? Can deeper fellowship (koinonia) and more direct community involvement (diakonia) constructively embody the gospel and foster church formation? The article indicates that, in light of frequent natural disasters, sharing God’s compassion in concrete ways has become vital to these churches’ existence. Christians face new challenges, as they deepen their involvement in existential challenges caused by disasters and other existing sociopolitical realities. The article explores the potential of missional-diaconal practices of local congregations and argues that diakonia in all its dimensions embodies the missio Dei and contributes to church formation in significant ways.